Study of drug resistance pattern among isolated strains of Mycobacterium tuberculosis against individual antimycobacterial drugs - Virendra Kashetty; Mangala Ghatole; Apeksha Ghule (Tropical Journal of Pathology and Microbiology, 2020)
Background: In the laboratory in-vitro antimycobacterial sensitivity testing is done conventionally by exposing the test strain to individual drugs by one of the recommended methods. Thus the present work was planned to assess the effects of various antimycobacterial drugs individually.Methods: The study included 73 strains of Mycobacterium tuberculosis isolated from 216 patients suffering from pulmonary tuberculosis and who visited the hospital for the first time and who had not received any antimycobacterial chemotherapy. From all these patients early morning spot sample was collected in a wide-mouthed sterile container and transported immediately to the laboratory.Result: Out of 73 stains, 62 (84.93%) were sensitive to all primary antimycobacterial agents and 11 (15.07%) were resistant to one or more drugs. 6 (8.22%) were resistant to Isoniazid (INH), 9 (12.33%) and 2 (2.74%) strains were resistant to Rifampicin (R’cin) and Streptomycin respectively. Overall resistance to a single drug was higher (8.22%) than to two drugs (5.48%) followed by three drugs (1.37%).Conclusion: Treatment of tuberculosis with appropriate drugs for a defined period is an important factor in the complete remission of disease in the individual patient, as well as in the management of the disease in a community.